Hard-Carbon Negative Electrodes from Biomasses for Sodium-Ion Batteries - Lu, Bin; Lin, Chengjun; Xiong, Haiji; Zhang, Chi; Fang, Lin; Sun, Jiazhou; Hu, Ziheng; Wu, Yalong; Fan, Xiaohong; Li, Guifang; Fu, Jile; Deng, Dingrong; et al. (Molecules (Basel, Switzerland), 2023)
With the development of high-performance electrode materials, sodium-ion batteries have been extensively studied and could potentially be applied in various fields to replace the lithium-ion cells, owing to the low cost and natural abundance. As the key anode materials of sodium-ion batteries, hard carbons still face problems, such as poor cycling performance and low initial Coulombic efficiency. Owning to the low synthesis cost and the natural presence of heteroatoms of biomasses, biomasses have positive implications for synthesizing the hard carbons for sodium-ion batteries. This minireview mainly explains the research progress of biomasses used as the precursors to prepare the hard-carbon materials. The storage mechanism of hard carbons, comparisons of the structural properties of hard carbons prepared from different biomasses, and the influence of the preparation conditions on the electrochemical properties of hard carbons are introduced. In addition, the effect of doping atoms is also summarized to provide an in-depth understanding and guidance for the design of high-performance hard carbons for sodium-ion batteries.